Comparative Invitro Sensitivity of Selected Chemicals on Phytophthora palmivora from Cocoa and Durian - Chan, Luz G.; Kwee, Lim Tong (1986)
Five new systemic compounds vzi. metalaxyl, benalayxl, cyprofuran, propamocarb and fosetyl A I and two standard protectants, etridiazole and captafol were compared for invitro effects on representative isolates of Phytophthora palmivora from cocoa and durian. MetalaxyI, etridiazole and cyprofuram were highly inhibitory to mycelial growth, sporangium and chlamydospore product£on, direct sporangium germination and germ-tube development of both cocoa and durian isolates while benalaxyl was moderately inhibitory. Etridiazole and benalaxyl were more suppressive 9n zoospore germination but metalaxyl and cyprofuram were relatively ineffective. Captafol was also highly suppressive to mycelz'al growth, direct sporangium and zoospore germination but less so on sporangium and chlamydospore production. Propamocarb and fosetyl Al were comparatively the least effective against all the developmental stages of the zsolates except in the case of zoospore germination of the durian isolate where the latter was highly inhibitory.